Exploring educational simulation platform features for addressing complexity in Industry 4.0: a qualitative analysis of insights from logistics experts - Pacheco-Velazquez, Ernesto; Rodes-Paragarino, Virginia; Marquez-Uribe, Alberto (Frontiers in Education, 2024)
Introduction This study explores the transformative impact of Industry 4.0 on industrial operations, emphasizing the integration of advanced technologies like AI, IoT, and Big Data Analytics to enhance process optimization, automation, and connectivity. Despite its potential for efficiency, Industry 4.0 introduces significant complexities, challenging existing operational and decision-making frameworks. Addressing these challenges, the research investigates the role of simulation platforms in logistics, seeking to identify their critical attributes for effective complexity management. It highlights the need for innovative tools in system evaluation, performance measurement, and skill development, aiming to equip the workforce with essential Industry 4.0 competencies. Through qualitative insights from logistics experts, the study aims to offer practical recommendations for educators and industry professionals, contributing to the design and implementation of educational simulations that align with the intricate demands of Industry 4.0 logistics. Methods This study employs a qualitative content analysis approach to develop an Industry 4.0-adapted logistics simulator, leveraging the Asteraceae framework for digital game co-design and pedagogical reflection. Data were collected from six industry and academia experts through semi-structured interviews, designed around the framework’s key steps to explore simulator design, decision-making, impact, and skill development. Utilizing convenience sampling, the research engaged participants with experience in educational logistics platforms and simulators. Interviews were conducted online, with ethical considerations including informed consent. Transcription used OpenAI’s API for accuracy, followed by manual review. The analysis combined qualitative content with frequency analysis, employing Atlas.ti software to identify and code key simulation features as informed by expert insights. This methodology underscores a comprehensive approach to understanding and innovating logistics education for Industry 4.0, aiming to equip learners with necessary competencies through targeted simulation tools. Results The study’s findings emphasize the critical role of simulation tools in Industry 4.0 logistics for risk mitigation, operational planning, and decision-making. Experts pointed out the significant benefits of simulations in providing safe spaces for experimentation, especially valuable for SMEs with limited access to advanced technologies. They advocated for simulators to incorporate current technological and e-commerce trends, suggesting a customizable business model based on diverse logistics requirements. Key insights included the necessity for adaptable simulation architectures to handle various operational variables, the importance of integrating multidisciplinary competencies like data analytics and strategic management, and the role of performance metrics in evaluating simulations and logistics operations. The analysis revealed essential features for an educational logistics simulator, highlighting the importance of operational knowledge, predictive analytics, and the need for a comprehensive tool that integrates technology, strategy, operations, and data analysis. This approach aims to equip users with the skills necessary for navigating the complexities of modern logistics, promoting a deep understanding of systems thinking and complex reasoning skills. Discussion The discussion centers on the essential requirement for a multidisciplinary approach in creating an educational logistics simulator for Industry 4.0, emphasizing the need for technological adaptability and operational efficiency. It highlights the importance of integrating advanced technologies and collaborative paradigms to enhance logistics operations and improve decision-making processes. The utility of simulation-based learning as a pedagogical tool is acknowledged, with an emphasis on its role in developing complex thinking and practical skills relevant to the digital transformation of the logistics sector. The discussion suggests that educational simulations are poised to play a pivotal role in preparing the workforce for Industry 4.0 challenges by bridging technological advancements and pedagogical strategies. However, it also points to the limitations of the current study, such as its sampling method and regional focus, and calls for future research to explore broader applications and the integration of comprehensive strategies to ensure the educational simulator’s effectiveness and relevance in a global context.